ARTISTIC EXPRESSION IN MAVLONO ATOIY’S GHAZALS AND TUYUKS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This article explores the work of Mavlono Atoiy, his place in classical Uzbek literature, and his artistic mastery. The folk style, simple language, aruz meter, and the use of tajnis (homonymy) employed in the poet's ghazals and tuyuks are analyzed using examples. The essence of Atoiy’s poetry and the experiences of the lyrical hero are also revealed.